Wildlife Conservation Society Birds of Brazil : The Atlantic Forest of Southeast Brazil, including São Paulo and Rio de Janeiro - Ridgely, Robert S. (Book collections on Project MUSE., 2016)
Brazil is the fifth largest country in the world and is one of the planet's richest places for bird diversity, especially when it comes to the number of endemic species. Brazil's Atlantic Forest region is one of the most dazzling of all. Immediately surrounding São Paulo and Rio de Janeiro, this area of Brazil is also a relatively accessible area to birders from around the world. In the Birds of Brazil Field Guides, the Wildlife Conservation Society brings together a top international team to do justice to the incredible diversity of Brazilian birds. This second guide presents 927 bird species, 863 illustrated, that occur in just the southeastern Atlantic Forest biome (Mata Atlântica in Portuguese). Of these species, 140 are endemic and 105 near endemic to just this region; 83 of these are threatened. Modern and compact, this field guide provides illustrations of unparalleled quality, key field marks, and regional range maps to facilitate easy recognition of all species normally occurring in this vibrant and critically important area of Brazil.